Diversité et usages des macromycètes de la Réserve de Biosphère de Luki (Kongo Central /République démocratique du Congo) - Charlot Mikobi Mikobi; Ernestine Lonpi Tipi; Bill Kasongo wa Ngoy Kashiki; Isaac Diansambu Makanua; Joseph Lumande Kasali; Baudouin Michel (VertigO)
Non-timber forest products including macro-fungi are an important source of food in forest regions of the world. Studies on edible fungi have been done in several places of the country, but no research has been conducted in the Luki Biosphere Reserve to date. The overall objective was to draw up a preliminary list of macromycetes and their uses by the communities living in the Luki Biosphere Reserve. Two linear transects of 5000m × 10m and 8000m × 10m crossing the selected plant formations served as sampling units for the inventory in three facies of the tropical forest: mature forest, secondary forest and fallow. Semi-structured ethnomycological surveys were conducted among 156 people chosen at random in the Mangala, Lemba, Tsumba Kituti, Kisavu, Kiobo, Kimbuya, Camp INERA-Luki and Manterne villages bordering the Luki Biosphere Reserve. In total, 33 species of macromycetes were inventoried, including 30 species used for food purposes, 3 species used for food and medicinal purposes, 2 species used exclusively for medicinal purposes and 2 species without use. Edible fungi are dominated by saprotrophs of the Pleurotaceae family and ectomycorrhizals of the Hydnaceae family. On the other hand, fungi for medicinal use are dominated by the Ganodermataceae family; mushrooms that combine both food and medicinal uses belong to the families of Schizophyllaceae, Lyophyllaceae and Auriculariaceae. Overall, the local populations of the Luki Biosphere Reserve are familiar with macromycetes for food and medicinal use. This study provides necessary information to take into account for a mushroom domestication program in the Luki biosphere reserve in order to cope with food insecurity and the effects of climate change already perceptible in this part of the country.